Investigating the use of AI for academic writing among EFL college students: A case study at English Education Study Program of Universitas Ahmad Dahlan Yogyakarta - Riviyanti; Bambang Widi Pratolo (Institut Agama Islam Negeri Palopo, 2025)
The rapid growth of Artificial Intelligence (AI) has transformed various educational practices, particularly in enhancing students’ academic writing. This study investigates the effectiveness of Grammarly, an AI-based writing assistant, in improving English as a Foreign Language (EFL) students’ academic writing. Using a descriptive qualitative case study, data were collected through semi-structured interviews with five university students who regularly used Grammarly in their writing tasks. Findings revealed that four participants reported noticeable improvements in grammar accuracy and writing structure, while three participants stated that Grammarly helped them expand their vocabulary and refine their writing style. Most participants agreed that Grammarly’s real-time feedback enhanced their writing fluency and self-assurance, allowing them to produce more coherent and polished academic texts. Furthermore, its instructional explanations enabled students to recognize and correct recurring errors, fostering independent learning and long-term writing competence. However, two participants expressed concern about over-reliance on the tool, emphasizing the importance of maintaining self-editing and critical thinking skills. Overall, Grammarly proved to be a valuable support system that bridges the gap between technology and language learning, helping students write more effectively. The study concludes that integrating AI tools such as Grammarly can complement traditional instruction by offering personalized, immediate feedback that promotes both accuracy and autonomy in writing. Future research is recommended to explore how AI-based applications can be further adapted to diverse academic contexts and writing disciplines to maximize their pedagogical potential.